Meningkatkan kemampuan Guru dalam menyusun RPP berbasis PPK melalui Workshop di MTs Nurul Hasanah, Kecamatan Bandar Laksamana, Kabupaten Bengkalis - Syukur, Syukur (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this study is to describe the ability of MTs Nurul Hasanah teachers to improve the PPK-based Learning Implementation Plan (Strengthening Character Education) using a workshop pattern. There are four activities in this study namely action plans, action implementation, observation and re-flection. The results showed that there was an increase in the ability of MTs teachers Nurul Hasanah in compiling KDP-based RPPs. Before the workshop was held, the average teacher's ability score was 73% with a good category. After the workshop, the average score increased to 98% with a very good category. The conclusion of this study is that the workshop can improve the ability of MTs Nurul Hasanah teach-ers in developing PPP-Based RPP.